5х²-6ху+5у²=29
7х²-8ху+7у²=43
--
5х²-10ху+5у²+4xy=29
7х²-14ху+7у²+6xy=43
--
5(x²-2ху+у²)+4ху=29
7(х²-2ху+у²)+6ху=43
5(x-у)²+4ху=29
7(х-у)²+6ху=43
замена
ху=а
(х-у)²=b
5b+4а=29 |*6
7b+6а=43 |*4
--
5b+4а=29 |*6
7b+6а=43 |*4
--
30b + 24a = 174
28b + 24a = 172
--
вычитаем
2b = 2
b = 1
5*1 + 4a = 29
4a = 24
a = 6
--
ху=6
(х-у)²=1
|x - y| = 1
1. x - y = 1
x = 1 + y
y(y + 1) = 6
y² + y - 6 = 0
D = 1 + 24 = 25
y12=(-1 +- 5)/2 = -3 2
y1 = -3 x1 = -2
y2 = 2 x2 = 3
2. x - y = -1
x = -1 + y
y(y - 1) = 6
y² - y - 6 = 0
D = 1 + 24 = 25
y12=(1 +- 5)/2 = 3 -2
y1 = 3 x1 = 2
y2 = -2 x2 = -3
ответ (-2, -3) (3,2) (2,3) (-3,-2)
I.
1) 18у⁵-12ху²+9у³= 3у²·(6у³-4х+3у)
2) - 14аb³с²-21a²bc²-28a³b²c= -7abc·(2b²c+3ac+4a²b)
II.
1) a(3x-2y)+b(3x-2y) = (3x-2y)·(a+b)
2) (x+3)(2y-1)-(x+3)(3y+2)= (x+3)·(2y-1-3y-2)=(x+3)·(-y-3) = - (x+3)·(y+3)
III.
1) 3x-x²=0
x· (3-x) = 0
x₁ = 0;
3-x = 0 => x₂ = 3
ответ: {0; 3}
2) y²+5y=0
y·(у+5) = 0
у₁ = 0
у+5=0 => y₂ = -5
ответ: {0; -5}
IV.
27³+3⁷ = (3³)³ + 3⁷ = 3⁹ + 3⁷ = 3⁷· (3² + 1) = 3⁷· (9+1) = 3⁷ · 10
Понятие "кратно 10" означает "деление на 10 нацело"
(3⁷·10) : 10 = 3⁷ Доказано!